Manajemen Kepariwisataan pada Praktikum Perjalanan Insentif Mahasiswa MICE PNJ Angkatan 2021 - Nafisa, Choiru; Wahyudi, Revica Chika; Syah, Firman; Mulia, Cynthia Alfira Paramitha; Gavriella S, Amanda (Bisnis Event, 2025)
This study discusses incentive trips organized by one of the vocational colleges, the Jakarta State Polytechnic (PNJ). In this case, D4 ​​MICE students master the practice of courses, especially regarding tourism management. The purpose of this study is to explain the implementation of incentive trips as a practicum for students of the PNJ MICE study program batch 2021 and to explain tourism management to manage incentive trips for the PNJ MICE study program batch 2021. The research method used by the author is qualitative research, with primary and secondary data collection methods. Primary data is data that is first collected from original sources through observation, interviews with participant representatives from students who take part in incentive trips, and notes while in the field. While secondary data comes from libraries or journals as a review of the theory of research preparation. From the explanation above, it can be concluded that the implementation of incentive trips as a practicum for students of the 2021 PNJ MICE study program can run smoothly with effective communication that has occurred so far. The implementation of communication during the bidding process to the evaluation is considered effective in making the incentive trip event process to Anyer Island carried out by the committee successful. Meanwhile, tourism management to manage incentive trips for the 2021 PNJ MICE study program requires caution, especially when making a decision. For example, in choosing bus transportation for travel incentives. On the other hand, the selection of accommodation is not only seen from star hotels. Keywords: Tourism Management, Incentive Trips, and D4 MICE PNJ.